Secondary batteries and electrical devices
By using graphitized carbon materials with a smaller specific surface area and an electrolyte containing carboxylic acid ester solvents in secondary batteries, combined with the strategy of controlling the content of small-particle size materials, the challenges of secondary batteries in both ratio and cycle are solved, and better battery performance is achieved.
Patent Information
- Application Number
- CN202410338847.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-22
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-03-22
AI Technical Summary
Existing secondary batteries have challenges in taking into account both rate and cycleability, especially in the rapid attenuation of capacity during large-scale discharge.
A secondary battery was designed, using graphitized carbon material with a relatively small specific surface area as the negative electrode active material, and used in conjunction with an electrolyte containing a carboxylic acid ester solvent and a film-forming stabilizer to control the content of the negative electrode active material in small particle size to reduce side reactions.
Significant progress has been made in improving the rate of secondary batteries, while effectively reducing the negative impact on cycling performance, achieving a design that takes into account both fast charging and cycling performance.
Smart Images

Figure CN118198469B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a secondary battery and an electrical device. Background Art
[0002] Secondary batteries are widely used in various consumer electronic products and electric vehicles due to their outstanding features such as light weight, no pollution, and no memory effect. Among them, lithium-ion batteries are widely used in portable electronic devices, electric vehicles and other fields.
[0003] As the application scope of secondary batteries becomes wider and wider, the requirements for battery performance are also getting higher and higher. Summary of the invention
[0004] The present application provides a secondary battery and an electrical device. The secondary battery designed in the present application is used to balance the comprehensive performance of the battery. For example, to a certain extent, it takes into account both cycle stability and fast charging performance.
[0005] The first aspect of the present application is to provide a secondary battery, comprising:
[0006] Negative electrode sheet: contains negative electrode active materials, which meet the following conditions:
[0007] (1.1) The specific surface area of the negative electrode active material is 0.5 m 2 / g~3.0m 2 / g;
[0008] (1.2) The volume distribution particle size of the negative electrode active material Dv1 ≥ 1.5 μm;
[0009] The negative electrode active material comprises a graphitized carbon material;
[0010] Electrolyte: contains carboxylic acid ester solvent and film-forming stabilizer.
[0011] The graphitized carbon material in this application has the characteristics of small specific surface area and small particle size particles as a negative electrode active material. The negative electrode active material with this characteristic is used in combination with an electrolyte containing a carboxylic acid ester solvent and a film-forming stabilizer. On the premise of improving the rate performance of the secondary battery, it can also reduce the impact on the battery cycle performance. Specifically, the specific surface area of the negative electrode active material provided in this application is relatively small, which can effectively reduce the side reaction between it and the electrolyte, and prepare for the use of carboxylic acid ester solvents. This is because carboxylic acid ester solvents have the advantages of low viscosity and low surface tension, which are easier to diffuse to the positive and negative electrode surfaces, and improve the wettability of the positive and negative electrode active materials to the electrolyte to accelerate the diffusion rate of lithium ions, thereby improving the rate performance of the battery. However, it also has obvious disadvantages: the probability of side reactions occurring on the positive and negative electrode surfaces is high, and gas production is high, which is not conducive to the cyclability of the battery. The present application chooses to use a negative electrode active material with a relatively small specific surface area + a film-forming stabilizer to reduce the probability of side reactions. At the same time, the present application also controls the content of small-particle negative electrode active materials, and further reduces side reactions by reducing their usage. On the other hand, in the original negative electrode active materials, small-particle materials will occupy the internal pores, making the lithium ion transmission path curved, thereby increasing the actual path length of lithium ions. The choice of controlling the content of small-particle negative electrode active materials in the present application also plays a positive role in improving the battery's rate capability. Therefore, the design method provided in the present application is conducive to taking into account both the fast charging performance and the cycle performance of the secondary battery.
[0012] In some embodiments of the present application, the specific surface area of the negative electrode active material is 0.5 m 2 / g~2.0m 2 / g;
[0013] and / or;
[0014] The volume distribution particle size Dv1 of the negative electrode active material is 1.9 μm to 3.1 μm.
[0015] In some embodiments of the present application, the graphitized carbon material satisfies at least one of the following:
[0016] (2.1) The orientation index OI value of the graphitized carbon material is ≤24; the orientation index OI value is the peak intensity value of the plane (110) and the plane (004) in the X-ray powder diffraction pattern of the graphitized carbon material;
[0017] (2.2) The volume distribution particle size of the graphitized carbon material satisfies: 7.5 μm ≤ Dv50 ≤ 20 μm, Dv10 ≥ 3.5 μm, Dv90 ≤ 40 μm.
[0018] In some embodiments of the present application, the graphitized carbon material satisfies at least one of the following:
[0019] (3.1) The orientation index of graphitized carbon materials satisfies: 10≤OI value≤22;
[0020] (3.2) The volume distribution particle size of the graphitized carbon material satisfies: 10μm≤Dv50≤18.5μm, 3.5μm≤Dv10≤7.0μm, Dv90≤40μm.
[0021] In some embodiments of the present application, the negative electrode active material further comprises amorphous carbon; the amorphous carbon comprises one or both of hard carbon and soft carbon;
[0022] and / or;
[0023] The volume distribution particle size of amorphous carbon satisfies: 3.5μm≤Dv50≤7.0μm;
[0024] and / or;
[0025] The graphitized carbon material includes one or more of natural graphite, artificial graphite, and composite graphite.
[0026] In some embodiments of the present application, the graphitized carbon material has a core-shell structure, the core of the core-shell structure comprises one or more of natural graphite, artificial graphite, and composite graphite, and the shell of the core-shell structure comprises an amorphous carbon coating layer.
[0027] In some embodiments of the present application, based on the total mass of the negative electrode active material, the mass percentage content of the graphitized carbon material is greater than 75%.
[0028] In some embodiments of the present application, the carboxylate solvent satisfies at least one of the following:
[0029] (4.1) Carboxylic acid ester has the following structural formula:
[0030] R1-COO-R2;
[0031] Wherein, R1 and R2 each independently comprise a substituted and / or unsubstituted C1-C5 alkyl group;
[0032] (4.2) Based on the mass of the electrolyte, the mass percentage content of the carboxylic acid ester is 5% to 70%;
[0033] In some embodiments of the present application, the carboxylate solvent satisfies at least one of the following:
[0034] (5.1) The carboxylic acid ester comprises one or more of ethyl acetate, methyl acetate, ethyl propionate, propyl acetate, methyl propionate, and methyl butyrate;
[0035] (5.2) Based on the mass of the electrolyte, the mass percentage content of the carboxylic acid ester is 10% to 60%.
[0036] In some embodiments of the present application, the electrolyte further comprises a carbonate solvent, and the carbonate solvent comprises one or more of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, vinylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0037] In some embodiments of the present application, the film-forming stabilizer satisfies at least one of the following:
[0038] (6.1) Based on the total mass of the electrolyte, the mass percentage content of the film-forming stabilizer is 0.02% to 6%.
[0039] (6.2) the film-forming stabilizer comprises one or more of a boron-containing lithium salt, a phosphorus-containing lithium salt and a sulfur-containing lithium salt;
[0040] and / or;
[0041] The boron-containing lithium salt includes one or more of lithium tetrafluoroborate, lithium bisoxalatoborate and lithium bisfluorooxalatoborate;
[0042] and / or;
[0043] The phosphorus-containing lithium salt includes one or more of lithium difluorophosphate, lithium fluorophosphate and lithium phosphate;
[0044] and / or;
[0045] The sulfur-containing lithium salt includes one or more of lithium fluorosulfonate, lithium sulfate, and lithium aminosulfonate.
[0046] In some embodiments of the present application, the film-forming stabilizer comprises lithium fluorosulfonate and lithium difluorophosphate. Based on the total mass of the electrolyte, the mass percentage content of lithium difluorophosphate is ≤1%, and the mass percentage content of lithium fluorosulfonate is greater than or equal to 0.1% and less than 2%.
[0047] In some embodiments of the present application, a positive electrode sheet is also included, the positive electrode sheet contains a positive electrode active material, and the specific surface area of the positive electrode active material is 8m 2 / g~17m 2 / g.
[0048] In some embodiments of the present application, the positive electrode active material comprises a lithium-containing transition metal phosphate; the lithium-containing transition metal phosphate comprises olivine-type lithium manganese iron phosphate, and the chemical formula of olivine-type lithium manganese iron phosphate is Li (1-x1) Fe x2 Mn (1-x2) PO4, where 0≤x1<1, 0≤x2≤1.
[0049] The second aspect of the present application is to provide an electrical device comprising the secondary battery described in the first aspect.
[0050] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0052] Figure 1 A schematic diagram of the structure of lithium ion diffusion paths in negative electrode active materials in the prior art;
[0053] Figure 2 A schematic diagram of the battery structure of some embodiments of the present application;
[0054] Figure 3 This is a schematic diagram of the exploded structure of batteries in some embodiments of the present application;
[0055] Figure 4 A schematic diagram of a vehicle structure of some embodiments of the present application;
[0056] Figure 5 A schematic diagram of the battery pack structure of some embodiments of the present application;
[0057] Figure 6 A schematic diagram of the structure of a negative electrode sheet in some embodiments of the present application;
[0058] Figure 7 This is a schematic diagram of the structure of another negative electrode plate of some embodiments of the present application.
[0059] The reference numerals in the specific implementation manner are as follows:
[0060] 10000, vehicles;
[0061] 1000, battery; 2000, controller; 3000, motor;
[0062] 100. Battery cell;
[0063] 200, box body; 210, first part; 220, second part;
[0064] 10. Secondary battery;
[0065] 101, housing; 102, electrode assembly; 103, cover plate;
[0066] 1. Negative electrode;
[0067] 11. Negative electrode current collector;
[0068] 12. Negative electrode film layer;
[0069] Coordinate axis x direction: length or width direction of the negative electrode;
[0070] Coordinate axis z direction: thickness direction of negative electrode sheet. DETAILED DESCRIPTION
[0071] Below, the embodiments of the electrode assembly, battery, and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0072] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0073] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0074] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0075] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0076] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0077] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0078] Unless otherwise specified, in this application, the terms "first", "second", etc. are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the quantity, specific order or primary and secondary relationship of the indicated technical features.
[0079] Unless otherwise specified, in this application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple sheets" refers to more than two sheets (including two sheets).
[0080] The term "alkyl" is expected to be a straight chain saturated hydrocarbon structure with 1 to 20 carbon atoms. "Alkyl" is also expected to be a branched or cyclic hydrocarbon structure with 3 to 20 carbon atoms. When specifying an alkyl with a specific carbon number, it is expected to cover all geometric isomers with that carbon number; therefore, for example, "butyl" means including n-butyl, sec-butyl, isobutyl, tert-butyl and cyclobutyl; "propyl" includes n-propyl, isopropyl and cyclopropyl. Alkyl examples include, but are not limited to methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, cyclobutyl, n-pentyl, isopentyl, neopentyl, cyclopentyl, methylcyclopentyl, ethylcyclopentyl, n-hexyl, isohexyl, cyclohexyl, n-heptyl, octyl, cyclopropyl, cyclobutyl, norbornyl, etc.
[0081] The term "substituted" includes the replacement of hydrogen atoms in the alkyl group by other groups, and the number of substitutions is determined by the number of hydrogen atoms.
[0082] Secondary batteries have been widely used in various products due to their advantages such as high energy density, long cycle life, safety and reliability. In recent years, with the significant increase in demand for secondary batteries as energy sources, higher requirements have been placed on the performance of secondary batteries, such as kinetic performance and cycle performance.
[0083] Graphite is the most commonly used negative electrode active material for secondary batteries, but the kinetic performance of graphite is poor, especially when discharged at a high rate, the capacity of the secondary battery decays rapidly.
[0084] The prior art discloses a variety of ways to improve the above problems, such as increasing the secondary particle content in graphite, reducing the particle size of graphite to shorten the lithium ion diffusion path, and improving the viscosity of the electrolyte, etc. However, while improving the kinetic performance, new problems will arise. How to balance the rate performance and cyclability of secondary batteries is the technical problem that this application actually aims to solve.
[0085] Based on the above considerations, in order to solve the problem that the comprehensive performance of secondary batteries needs to be improved, a secondary battery and an electric device are obtained according to the above design concept and related experimental research.
[0086] The secondary battery provided in the present application comprises a negative electrode plate and an electrolyte, wherein the negative electrode plate comprises a negative electrode active material, wherein the negative electrode active material comprises a graphitized carbon material, and the negative electrode active material satisfies the following conditions: (1.1) The specific surface area of the negative electrode active material is 0.5 m 2 / g~3.0m 2 / g; (1.2) the volume distribution particle size Dv1 of the negative electrode active material is ≥1.5μm; and the electrolyte contains a carboxylic acid ester solvent and a film-forming stabilizer.
[0087] The graphitized carbon material in this application has the characteristics of small specific surface area and small particle size particles as a negative electrode active material. The negative electrode active material with this characteristic is used in combination with an electrolyte containing a carboxylic acid ester solvent and a film-forming stabilizer. On the premise of improving the rate performance of the secondary battery, it can also reduce the impact on the battery cycle performance. Specifically, the specific surface area of the negative electrode active material provided in this application is relatively small, which can effectively reduce the side reaction between it and the electrolyte, and prepare for the use of carboxylic acid ester solvents. This is because carboxylic acid ester solvents have the advantages of low viscosity and low surface tension, which are easier to diffuse to the positive and negative electrode surfaces, and improve the wettability of the positive and negative electrode active materials to the electrolyte to accelerate the diffusion rate of lithium ions, thereby improving the rate performance of the battery. However, it also has obvious disadvantages: the probability of side reactions occurring on the positive and negative electrode surfaces is high, and gas production is high, which is not conducive to the cyclability of the battery. The present application chooses to use a negative electrode active material with a relatively small specific surface area + a film-forming stabilizer to reduce the probability of side reactions. At the same time, the present application also controls the content of small-particle negative electrode active materials, and further reduces side reactions by reducing their usage. On the other hand, in the original negative electrode active materials, small-particle materials will occupy the internal pores, making the lithium ion transmission path tortuous, thereby increasing the actual path length of lithium ions. For details, please refer to the attached drawings of the specification. Figure 1 Lt is the actual path length of lithium ions in the negative electrode active material layer, combined with Figure 1 It can be seen that due to the presence of small-particle materials, Lt increases. The application selects to control the content of small-particle negative electrode active materials, which also plays a positive role in improving the rate performance of the battery. Therefore, the design method provided by the application is conducive to taking into account the fast charging performance and cycle performance of the secondary battery.
[0088] The secondary battery provided in the present application has improved rate capability and can be used for high current charging and discharging. For example, the secondary battery has high cycle stability, which can ultimately improve the experience of battery users. The secondary battery may include an outer packaging. The outer packaging can be used to encapsulate electrode assemblies and electrolytes. The outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and as plastics, polypropylene, polybutylene terephthalate, and polybutylene succinate, etc. may be listed.
[0089] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 2 The secondary battery 10 is a square structure as an example.
[0090] According to some embodiments of the present application, Figure 3, the outer packaging may include a shell 101 and a cover plate 103. Among them, the shell 101 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 101 has an opening connected to the receiving cavity, and the cover plate 103 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 102 through a winding process or a lamination process. The electrode assembly 102 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 102. The number of electrode assemblies 102 contained in the secondary battery 10 can be one or more, and those skilled in the art can select according to specific actual needs.
[0091] The secondary battery provided in the present application is beneficial to improving battery performance. The secondary battery can be used as a power source for an electrical device or as an energy storage unit for an electrical device. The electrical device is applied to the power field, such as mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but not limited to the above-mentioned fields.
[0092] For the convenience of explanation, some embodiments of the present application are described by taking the electric device as a vehicle as an example. The negative electrode plate provided by the present application is applied to the vehicle battery. Since the battery has good power performance, the vehicle starts faster. On the other hand, the battery has high energy density, so it can provide the vehicle with a longer cruising range within an effective space.
[0093] Please refer to Figure 4 , Figure 4 A schematic diagram of the structure of a vehicle 10000 provided for some embodiments of the present application. The vehicle 10000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 1000 is provided inside the vehicle 10000, and the battery 1000 may be provided at the bottom, head or tail of the vehicle 10000. The battery 1000 may be used to power the vehicle 10000, for example, the battery 1000 may be used as an operating power source for the vehicle 10000. The vehicle 10000 may also include a controller 2000 and a motor 3000, and the controller 2000 is used to control the battery 1000 to power the motor 3000, for example, for the starting, navigation and working power requirements of the vehicle 10000 during driving.
[0094] In some embodiments of the present application, the battery 1000 can not only serve as the operating power source of the vehicle 10000, but also serve as the driving power source of the vehicle 10000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 10000.
[0095] Please refer to Figure 5, Figure 5 The exploded diagram of the battery 1000 provided in some embodiments of the present application. The battery 1000 includes a housing 200 and a battery cell 100. Conventional battery cells include primary batteries or secondary batteries. The present application specifically protects secondary batteries. The battery cell 100 is accommodated in the housing 200. The housing 200 is used to provide a storage space for the battery cell 100. The housing 200 can adopt a variety of structures.
[0096] In some embodiments, the box body 200 may include a first part 210 and a second part 220, the first part 210 and the second part 220 cover each other, and the first part 210 and the second part 220 jointly define a storage space for accommodating the secondary battery 100. The second part 220 may be a hollow structure with one end open, and the first part 210 may be a plate-like structure, and the first part 210 covers the open side of the second part 220, so that the first part 210 and the second part 220 jointly define a storage space; the first part 210 and the second part 220 may also be hollow structures with one side open, and the open side of the first part 210 covers the open side of the second part 220. Of course, the box body 200 formed by the first part 210 and the second part 220 may be in various shapes, such as a cylinder, a cuboid, etc.
[0097] In the battery 1000, there may be multiple battery cells 100, and the multiple battery cells 100 may be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 100 are both connected in series and in parallel. The multiple battery cells 100 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 100 is accommodated in the box 200; of course, the battery 1000 may also be a battery 1000 module formed by connecting multiple battery cells 100 in series, in parallel, or in a mixed connection, and then the multiple battery 1000 modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 200. The battery 1000 may also include other structures, for example, the battery 1000 may also include a busbar component for realizing electrical connection between the multiple battery cells 100.
[0098] Secondary battery
[0099] The present application discloses a secondary battery in some embodiments, wherein the secondary battery comprises a negative electrode plate and an electrolyte, wherein the negative electrode plate comprises a negative electrode active material, wherein the negative electrode active material comprises a graphitized carbon material, and wherein the negative electrode active material satisfies the following conditions: (1.1) the specific surface area of the negative electrode active material is 0.5 m 2 / g~3.0m 2 / g; (1.2) the volume distribution particle size Dv1 of the negative electrode active material is ≥1.5μm; and the electrolyte contains a carboxylic acid ester solvent and a film-forming stabilizer.
[0100] The graphitized carbon material of the present application is a carbon material, and the carbon material mainly contains carbon elements. And the carbon material contains graphite, which can be a single type of graphite, or a mixture of multiple graphites, or a mixture of graphite and other carbon materials. The graphitized carbon material has good conductivity and stability, so the present application chooses it as the negative electrode active material.
[0101] The specific surface area of the present application includes any conventional meaning in the art, and can be obtained by testing using instruments or methods known in the art, such as testing the specific surface area using a gas adsorption method, specifically referring to the standard test of GB / T19587-2017.
[0102] The specific surface area of the negative electrode active material selected in this application is 0.5 m 2 / g~3.0m 2 / g, compared with conventional carbon materials in the art, the specific surface area is reduced, which may be affected by the type and properties of the carbon material selected in this application. This application will discuss the types and preparation methods of carbon materials in detail below. This application discloses in these embodiments that the specific surface area of the negative electrode active material can be 0.5m 2 / g, 0.8m 2 / g, 1.0m 2 / g, 1.2m 2 / g, 1.5m 2 / g, 1.8m 2 / g, 2.0m 2 / g, 2.5m 2 / g, 3.0m 2 / g or any of the above ranges. This application selects a specific surface area of 0.5m 2 / g~3.0m 2 / g of negative electrode active material can be conveniently used in combination with carboxylic acid ester solvents and film-forming stabilizers to improve the comprehensive performance of the battery of the present application.
[0103] The volume distribution particle size Dv1 of the present application has the same meaning as the conventional Dv50 in the art, specifically referring to the volume of particles with a particle size smaller than it accounting for 1%. The measurement method of Dv1 can refer to Dv50, using the conventional measurement method in the art, such as using a particle size analyzer to measure the particle size distribution and then obtain it by statistics. In these embodiments, the present application chooses to refer to the laser diffraction particle size analysis method for determination, specifically referring to the standard GB / T19077-2016 to obtain a particle size distribution diagram, and then obtains it by statistics and calculation. In these embodiments, the present application discloses that the volume of particles with a particle size less than 1.5 μm accounts for 1%. The present application controls the content of small-particle-sized negative electrode active materials, and further reduces side reactions by reducing their usage. On the other hand, in the original negative electrode active material, the small-particle-sized material will occupy the internal pores, making the lithium ion transmission path bend, thereby increasing the actual path length of the lithium ions. Therefore, controlling the content of small-particle-sized negative electrode active materials also plays a positive role in improving the rate performance of the battery.
[0104] The carboxylate solvents of the present application include those having carboxylate groups. Carboxylate solvents have the advantages of low viscosity and small surface tension, and they are easier to diffuse to the surface of the positive and negative electrodes, and improve the wettability of the positive and negative electrode active materials to the electrolyte to accelerate the diffusion rate of lithium ions, thereby improving the rate capability of the battery. However, it also has obvious disadvantages: the probability of side reactions occurring on the surfaces of the positive and negative electrodes is high, and a lot of gas is produced, which is not conducive to the cyclability of the battery. The present application selects carboxylate solvents to be used in combination with negative electrode active materials with relatively small specific surface areas, which is beneficial to taking into account both the fast charging performance and the cycling performance of the secondary battery.
[0105] The film-forming stabilizer of the present application includes an additive that facilitates the improvement of the reaction between the carboxylic acid ester solvent and the positive and negative electrode active materials, thereby improving the cycle stability of the battery and being used for high-rate charge and discharge by improving the stability of the interface film.
[0106] In summary, the graphitized carbon material in the present application has the characteristics of small specific surface area and few small-size particles as a negative electrode active material. The negative electrode active material with such characteristics is used in combination with an electrolyte containing a carboxylic acid ester solvent and a film-forming stabilizer. On the premise of improving the rate performance of the secondary battery, it can also reduce the impact on the battery cycle performance.
[0107] In some embodiments of the present application, the specific surface area of the negative electrode active material is 0.5 m 2 / g~2.0m 2 / g.
[0108] In these embodiments, the present application further adjusts the specific surface area of the negative electrode active material to better match the electrolyte.
[0109] In some embodiments of the present application, the volume distribution particle size Dv1 of the negative electrode active material is 1.9 μm to 3.1 μm.
[0110] In these embodiments, the present application further clarifies the upper limit value of the volume distribution particle size Dv1, that is, the volume or number of particles with a particle size less than or equal to 3.1 μm only accounts for 1%, and the volume or number of negative electrode materials with smaller particle sizes is controlled. On the one hand, it is used to match the specific value of the specific surface area of the above-mentioned negative electrode active material, and on the other hand, it also prepares for improving the overall performance of the battery.
[0111] In some embodiments of the present application, the graphitized carbon material satisfies at least one of the following:
[0112] (2.1) The orientation index OI value of graphitized carbon material is ≤24;
[0113] (2.2) The volume distribution particle size of the graphitized carbon material satisfies: 7.5 μm ≤ Dv50 ≤ 20 μm, Dv10 ≥ 3.5 μm, Dv90 ≤ 40 μm.
[0114] The orientation index OI value of the graphitized carbon material in this application includes the graphite orientation degree, which is mainly used to characterize the overall isotropic degree of graphite. The peak intensity values of the face (110) and face (004) of the graphite crystal can be obtained by performing X-ray diffraction on the graphitized carbon material, and the orientation index OI value can be obtained by calculating the peak integral area ratio of the two crystal faces. In general, the graphite orientation degree is affected by the structural characteristics of the material itself, and the smaller the value of the graphite orientation degree, the more conducive it is for lithium ions to diffuse inside it, and the problems such as the cyclic expansion of the battery will be better improved, but the orientation index OI value will also affect the compaction density and capacity of the battery. If it is too low, it will cause low compaction density and low capacity. Compared with the conventional graphitized carbon material used to improve the battery rate, the orientation index OI value of the material of this application is relatively higher, because the application also takes into account other battery properties, and it is necessary to take into account the actual improvement degree of the rate of carboxylic acid ester solvents. The present application discloses in these embodiments that the orientation index OI value of the graphitized carbon material can be any one of 24, 22, 20, 18, 16, 14, 12, 10, 8 or any one of the values satisfying the above ranges.
[0115] The meanings of the volume distribution particle sizes Dv50, Dv10 and Dv90 of the graphitized carbon material of the present application have the same meaning as the volume distribution particle size Dv1 of the above-mentioned negative electrode active material, among which Dv50 includes 50% of the volume of particles with a particle size greater than it and 50% of the volume of particles smaller than it, also known as the median diameter, which is usually used to indicate the average particle size of the particles. Dv10 includes 10% of the volume of particles with a particle size smaller than it, and Dv90 includes 90% of the volume of particles with a particle size smaller than it. Whether it is Dv50, Dv10 or Dv90, the measurement and calculation methods are the same as above, such as using a particle size analyzer to measure the particle size distribution of the graphitized carbon material and then obtain it by statistics. In these embodiments, the present application selects to refer to the laser diffraction particle size analysis method for determination, specifically refers to the standard GB / T19077-2016 to obtain the particle size distribution diagram, and then obtains it by calculation. The present application discloses in these embodiments that the volume distribution particle size of the graphitized carbon material satisfies: 7.5μm≤Dv50≤20μm, Dv10≥3.5μm, Dv90≤40μm, that is, the average particle size of the graphitized carbon material is 7.5μm to 20μm. Compared with the conventionally used carbon materials, the particle size of the graphitized carbon material provided in the present application has increased, and the graphitized carbon material with this particle size is convenient to meet the above requirements for negative electrode active materials with relatively small specific surface areas. The present application discloses in these embodiments that the Dv50 of the graphitized carbon material is any one of 7.5μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm or any one of the above range values.
[0116] In some embodiments of the present application, the graphitized carbon material satisfies at least one of the following:
[0117] (3.1) The orientation index of the graphitized carbon material satisfies: 10≤OI value≤22.
[0118] (3.2) The volume distribution particle size of the graphitized carbon material satisfies: 10μm≤Dv50≤18.5μm, 3.5μm≤Dv10≤7.0μm, Dv90≤40μm.
[0119] The orientation index of the graphitized carbon material of the present application should not be too small. The present application selects 10≤OI value≤22 for better matching with the electrolyte.
[0120] At the same time, the present application discussed above the control of the volume or quantity of small-particle negative electrode active materials, so the particle size uniformity of the graphitized carbon material has been relatively greatly improved, and this particle size improvement is obviously beneficial for reducing side reactions and improving rate capability.
[0121] In some embodiments of the present application, the negative electrode active material further includes amorphous carbon; the amorphous carbon includes any one of hard carbon or soft carbon.
[0122] The present application has discussed above that the negative electrode active material includes a graphitized carbon material, which may only include a graphitized carbon material, and the graphitized carbon material meets the above requirements of having a smaller specific surface area and particle size. At the same time, the negative electrode active material may also include amorphous carbon, which has a relatively low degree of graphitization, such as hard carbon. On the one hand, hard carbon is combined with graphitized carbon materials to meet the above requirements for a smaller specific surface area and particle size. On the other hand, the use of hard carbon can improve the current distribution of the negative electrode, thereby improving the rate and cyclability of the graphitized material.
[0123] In some embodiments of the present application, the volume distribution particle size of the amorphous carbon satisfies: 3.5 μm≤Dv50≤7.0 μm.
[0124] The volume distribution particle size Dv50 of the amorphous carbon in this application has the same meaning as the volume distribution particle size Dv50 of the above-mentioned graphitized carbon material. Among them, Dv50 includes 50% of the volume of particles with a particle size greater than it, and 50% of the volume of particles smaller than it, which is also called the median diameter, and is usually used to represent the average particle size of the particles. The measurement and calculation methods are the same as above, for example, a particle size analyzer is used to measure the particle size distribution of the graphitized carbon material and then obtain it by statistics. In these embodiments, the present application selects to refer to the laser diffraction particle size analysis method for determination, specifically refers to the standard GB / T19077-2016 to obtain the particle size distribution diagram, and then obtains it by calculation. The volume distribution particle size of amorphous carbon selected in this application satisfies: 3.5μm≤Dv50≤7.0μm. Compared with the average particle size of the graphitized carbon material, the particle size of the amorphous carbon selected for use in this application is relatively small, but it cannot be too small, because it is consistent with the idea of controlling the content of small-particle-size negative electrode materials in this application. At the same time, the relatively small particle size of amorphous carbon is added inside the graphitized carbon material, which can average the porosity of the graphitized carbon material to improve the current distribution, thus helping to further improve the rate capability of the battery.
[0125] In some embodiments of the present application, the graphitized carbon material includes one or more of natural graphite, artificial graphite, and composite graphite.
[0126] The composite graphite of the present application can also be called modified graphite, which is obtained by further modification on the basis of artificial graphite. In some embodiments of the present application, the graphitized carbon material is discussed in detail as artificial graphite, and the preparation method of the artificial graphite comprises: providing raw materials, crushing and shaping → granulation → graphitization treatment → surface roughening treatment to obtain artificial graphite materials. The raw materials of the present application in these embodiments can be one or more of raw coke and calcined coke; preferably, the raw materials include one or more of needle-shaped raw petroleum coke, non-needle-shaped raw petroleum coke, needle-shaped coal-based raw coke, non-needle-shaped coal-based raw coke, calcined needle coke, and calcined petroleum coke. The crushing of the present application can be carried out by devices and methods known in the art, such as air flow crushers, mechanical crushers or roller mills. A large number of too small particles are usually produced during the crushing process, and sometimes too large particles are also produced. Therefore, after crushing, classification can be performed as needed to remove too small particles and too large particles in the crushed powder. After classification, a particle product with a good particle size distribution can be obtained to facilitate subsequent molding and / or granulation processes. Classification can be performed by devices and methods known in the art, such as grading screens, gravity classifiers or centrifugal classifiers. The shaping of the present application can be performed by equipment (such as a molding machine or other molding equipment) and methods known in the art. For example, the edges and corners of the obtained granular product are polished to facilitate subsequent operations and to make the obtained product have higher stability. The granulation of the present application includes granulation using devices known in the art such as a granulator. The granulator generally includes a temperature control module for a stirred reactor and a reactor. In addition, the volume median particle size of the obtained product can be controlled by adjusting the process conditions such as stirring speed, heating speed, granulation temperature and cooling speed during the granulation process. The graphitization treatment of the present application includes high-temperature graphitization treatment and low-temperature graphitization treatment. In some embodiments, any one or two of high-temperature graphitization treatment and low-temperature graphitization treatment can be appropriately selected for treatment according to actual specific needs. Alternatively, high-temperature graphitization treatment and / or low-temperature graphitization treatment can be repeated. Graphite with an appropriate degree of graphitization and graphite interlayer spacing can be obtained by high-temperature graphitization treatment. Graphite prepared at an appropriate graphitization temperature can obtain an appropriate graphitization degree and graphite interlayer spacing, so that the composite artificial graphite obtains higher structural stability and gram capacity. The surface roughening treatment of the present application includes using conventional treatment methods in the art, such as physical methods.
[0127] The present application discloses in some embodiments a method for preparing artificial graphite, comprising the following steps:
[0128] S1: Feed the raw materials to the crusher through a vibrating feeder for coarse crushing, then send the qualified materials to the mechanical mill for fine crushing, use a grading screen to remove particles with a Dv50 of less than 1.5μm, and then polish the obtained particles to obtain a precursor with a Dv50 of 5μm to 25μm;
[0129] S2: Add the precursor obtained in step S1 to a reaction kettle, and add 8% to 15% of a binder asphalt (Dv50 is 5 μm to 8 μm) relative to the weight of the precursor for granulation for granulation, stir at a speed of 1000 r / min to 1500 r / min, heat at room temperature to 550°C to 570°C at a rate of 10°C / min, and then keep the temperature constant for 5 to 10 hours, granulate to a Dv50 of 10 μm to 30 μm, and obtain intermediate 1;
[0130] S3: Add the intermediate 1 obtained in step S2 into a graphitization furnace, heat it to 2100°C to 2200°C for graphitization, and sieve it with a 200-mesh sieve to obtain an artificial graphite with a volume distribution particle size satisfying: 7.5μm≤Dv50≤20μm, Dv10≥3.5μm, Dv90≤40μm.
[0131] In some embodiments of the present application, the graphitized carbon material has a core-shell structure, the core of the core-shell structure comprises one or more of natural graphite, artificial graphite, and composite graphite, and the shell of the core-shell structure comprises an amorphous carbon coating layer.
[0132] The present application discloses in these embodiments that the artificial graphite obtained in the above embodiments is further mixed with a coating agent in a certain mass ratio or preheated and then carbonized to obtain a graphitized carbon material with an amorphous carbon coating layer coated on the surface. The present application discloses in these embodiments that the coating agent includes but is not limited to conventional carbon source gas (volume percentage is 10% to 15%), such as methane, ethylene, acetylene, etc. The carbonization treatment of the present application is preferably carried out in an inert atmosphere furnace, and the temperature is controlled between 700°C and 1800°C. The graphitized carbon material with an amorphous carbon coating layer on the surface provided by the present application has a decreased specific surface area and a more uniform particle size distribution compared to the uncoated carbon material, and due to the isolation of the amorphous carbon coating layer, the probability of side reactions is also reduced.
[0133] In some embodiments of the present application, based on the total mass of the negative electrode active material, the mass percentage content of the graphitized carbon material is greater than 75%. The present application discloses in these embodiments that the mass percentage content of the graphitized carbon material can be any one of 78%, 80%, 85%, 90%, 95%, and 100%.
[0134] The present application discloses in some embodiments that the negative electrode active material only contains artificial graphite, and the mass percentage content of the artificial graphite is 100%.
[0135] In some embodiments, the present application discloses that the negative electrode active material includes artificial graphite and hard carbon, wherein the mass percentage of artificial graphite in the negative electrode active material is greater than 75%, and the rest is hard carbon.
[0136] The present application discloses in some embodiments that the negative electrode active material has a core-shell structure, the core of the core-shell structure includes artificial graphite, the shell of the core-shell structure includes an amorphous carbon coating layer, and the final core-shell structure negative electrode active material is modified graphite, in which the mass percentage of artificial graphite in the negative electrode active material is greater than 75%, and the rest is an amorphous carbon coating layer. The thickness of the amorphous carbon coating layer can be obtained by obtaining a transmission electron microscope image of the negative electrode active material, and the content of graphitized carbon material in the negative electrode active material can be obtained according to the thickness of the amorphous carbon coating layer and in combination with the X-ray photoelectron spectroscopy analysis spectrum of the negative electrode active material. Among them, the transmission electron microscope image and the X-ray photoelectron spectroscopy analysis spectrum are obtained by using conventional instruments and testing methods in the art.
[0137] The present application discloses in some embodiments that the thickness of the amorphous carbon coating layer is between 10 nm and 20 nm. The amorphous carbon coating layer having such a thickness is beneficial to reducing the probability of side reactions occurring therein.
[0138] The negative electrode active material of the present application is mixed with a conductive agent, a thickener, a binder, etc. according to a certain mass ratio and a solvent to form a negative electrode slurry. After the negative electrode slurry is defoamed, it is evenly coated on one or two surfaces of the negative electrode current collector and dried. Figure 6 , Figure 7 As shown in the figure, a negative electrode sheet including a negative electrode film layer is obtained. The solvent here includes but is not limited to water.
[0139] The conductive agent in the present application includes but is not limited to one or a combination of two of graphite, superconducting carbon, carbon black (such as acetylene black, Ketjen black, Super P, etc.), carbon dots, carbon nanotubes, graphene and carbon nanofibers; the thickener includes cellulose and its sodium salt, cellulose includes methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, etc.; the binder includes but is not limited to polyvinyl alcohol, polyethylene glycol, sodium carboxymethyl cellulose, polyethylene oxide, polyacrylic acid, polyacrylamide, sodium alginate, styrene-butadiene rubber (SBR), etc.
[0140] The present application discloses, in some embodiments, a mass ratio of the negative electrode active material, the conductive agent, the thickener and the binder: (90-97): (0.5-3): (0.5-3): (0.5-3).
[0141] The present application discloses in some embodiments that the negative electrode current collector includes but is not limited to a metal foil or a composite current collector, the metal foil may be a copper foil, and the composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and the like.
[0142] In some embodiments of the present application, the carboxylate solvent satisfies at least one of the following:
[0143] (4.1) Carboxylic acid ester has the following structural formula:
[0144] R1-COO-R2;
[0145] Wherein, R1 and R2 each independently comprise a substituted and / or unsubstituted C1-C5 alkyl group;
[0146] (4.2) Based on the mass of the electrolyte, the mass percentage content of the carboxylic acid ester is 5% to 70%.
[0147] The solvent of the present application includes carboxylic acid esters, which are relatively stable, not easily oxidized and reduced, and have good compatibility with the above-mentioned lithium salts and additives. At the same time, when carboxylic acid esters are included in the solvent, the electrolyte can have a lower viscosity and a smaller surface tension. It is combined with lithium-containing transition metal phosphates having relatively more lithium ion diffusion channels to facilitate full and effective contact between lithium-containing transition metal phosphates and electrolytes to improve the rate performance of the battery. The carboxylates selected in these embodiments of the present application are mainly linear carboxylates, because linear carboxylates have lower melting points and viscosities, so as to better cooperate with the positive electrode active material: lithium-containing transition metal phosphates. The present application also discloses in these embodiments that the mass percentage content of carboxylic acid esters is 5% to 70%, wherein the mass percentage content of carboxylic acid esters can be any one of 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or any one of the above range values.
[0148] In some embodiments of the present application, the carboxylate solvent satisfies at least one of the following:
[0149] (5.1) The carboxylic acid ester comprises one or more of ethyl acetate, methyl acetate, ethyl propionate, propyl acetate, methyl propionate, and methyl butyrate;
[0150] (5.2) Based on the mass of the electrolyte, the mass percentage content of the carboxylic acid ester is 10% to 60%.
[0151] As an example of carboxylic acid ester, carboxylic acid ester includes one or more of ethyl acetate, methyl acetate, ethyl propionate, propyl acetate, methyl propionate, and methyl butyrate. Carboxylic acid ester solvents have relatively lower viscosity, and when multiple carboxylic acid ester solvents are used in combination, the electrolyte can have a lower surface tension.
[0152] In some embodiments of the present application, the electrolyte further includes a carbonate solvent, and the carbonate solvent includes one or more of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, vinylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0153] The lithium salt selected in the present application has better solubility in carbonates than in carboxylates, so the present application chooses to use carboxylates in combination with carbonates to reduce the viscosity and melting point of the electrolyte without affecting the solubility of the lithium salt, thereby facilitating use with lithium-containing transition metal phosphates.
[0154] As an example of carbonate, carbonate includes one or more of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, vinylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. Selecting the carbonate as an example is conducive to better use with carboxylic acid ester.
[0155] In some embodiments of the present application, the film-forming stabilizer satisfies at least one of the following:
[0156] (6.1) In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage content of the film-forming stabilizer is 0.02% to 6%;
[0157] (6.2) the film-forming stabilizer comprises one or more of a boron-containing lithium salt, a phosphorus-containing lithium salt and a sulfur-containing lithium salt;
[0158] (6.3) boron-containing lithium salts include one or more of lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB) and lithium bis(fluorooxalatoborate) (LiDFOB);
[0159] (6.4) Phosphorus-containing lithium salts include one or more of lithium difluorophosphate (LiPO2F2), lithium fluorophosphate (Li2PO3F) and lithium phosphate (Li3PO4);
[0160] (6.5) The sulfur-containing lithium salt includes one or more of lithium fluorosulfonate (LiFSO3), lithium sulfate (Li2SO4), and lithium aminosulfonate (LiSO3NH2).
[0161] The content of the film-forming stabilizer in the present application is controlled to be 0.02% to 6% according to the solubility of various types and the actual degree of improvement of film formation in the electrolyte. The present application discloses in these embodiments that the mass percentage content of the film-forming stabilizer can be any one of 0.02%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6% or any one of the above range values.
[0162] In the present application, boron-containing lithium salts are lithium salts with B atoms as central atoms, which can be coordinated with alkoxy, ortho-diphenol, ortho-hydroxyl, carboxylic acid, etc. to form anionic complexes, and anionic complexes are mainly large π conjugated structures, and the negative charge distribution of the central ion is relatively dispersed, and its charge is delocalized, and the anionic radius is relatively large, making it difficult for anions to form ion pairs with strong binding force with lithium ions in organic solvents, and its solubility is relatively good. The more electron-withdrawing groups there are in the anionic complex, the more stable the anionic structure, the higher the solubility of lithium ions in the electrolyte, and the more conducive to improving the conductivity of the electrolyte. And boron-containing lithium salts can form SEI films with excellent performance on the surface of negative electrode active materials, and SEI films have organic solvent insolubility, can stably exist in organic electrolytes, can effectively reduce the solvent molecules in the electrolyte and embed them into the negative electrode active materials, so as to ensure the structural stability of the negative electrode active materials, and then improve the cycle performance of secondary batteries.
[0163] The phosphorus-containing lithium salt additive in the present application has a relatively large anion group and a high ionic conductivity, which is conducive to further improving the kinetic performance of the electrolyte, and the phosphorus-containing lithium salt additive can form a CEI film on the surface of the positive electrode active material. The CEI film formed has high lithium ion conductivity, which can significantly inhibit the continuous decomposition of the electrolyte and reduce the dissolution of transition metal ions in the positive electrode active material, thereby improving the cycle performance of the secondary battery. In addition, the phosphorus-containing lithium salt additive can also form an SEI film on the surface of the negative electrode active material, which has a low interfacial impedance, thereby significantly improving the cycle performance of the battery.
[0164] The sulfur-containing lithium salt additive in the present application has good antioxidant properties, high thermal stability, is insensitive to water in the electrolyte, and is not prone to side reactions; and the sulfur-containing lithium salt additive has a relatively high conductivity, which is beneficial to improving the migration rate of lithium ions, thereby improving the kinetic properties of the electrolyte.
[0165] As an example of a boron-containing lithium salt, the boron-containing lithium salt may include one or more of lithium tetrafluoroborate (LiBF4), lithium bis(C2O4)2 (LiBOB for short) and lithium bis(C2O4)2 (LiDFOB for short). Similarly, as an example of a phosphorus-containing lithium salt, the phosphorus-containing lithium salt may include one or more of lithium difluorophosphate (LiPO2F2), lithium fluorophosphate (Li2PO3F) and lithium phosphate (Li3PO4). As an example of a sulfur-containing lithium salt, the sulfur-containing lithium salt may include one or more of lithium fluorosulfonate (LiFSO3), lithium sulfate (Li2SO4) and lithium aminosulfonate (LiSO3NH2).
[0166] In some embodiments of the present application, the film-forming stabilizer comprises lithium fluorosulfonate and lithium difluorophosphate. Based on the total mass of the electrolyte, the mass percentage content of lithium difluorophosphate is ≤1%, and the mass percentage content of lithium fluorosulfonate is greater than or equal to 0.1% and less than 2%.
[0167] The present application selects lithium fluorosulfonate and lithium difluorophosphate as film-forming stabilizers to be added to the electrolyte at the same time to better match the above-mentioned lithium salts. On the other hand, the solubility of each film-forming stabilizer in the solvent is certain. For example, the solubility of lithium difluorophosphate in organic solvents is not high. For example, the content in carbonate solvents is about 1%, and the content in carboxylates such as ethyl acetate is about 3% to 4%. Continuing to increase its content will easily cause the electrolyte to become turbid. In these embodiments, the present application controls the mass percentage content of lithium difluorophosphate to be ≤1%, and the mass percentage content of lithium fluorosulfonate to be greater than or equal to 0.1% and less than 2%.
[0168] In addition to the above-mentioned carboxylic acid ester solvent and film-forming stabilizer, the electrolyte of the present application also contains a lithium salt, which includes but is not limited to one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).
[0169] The specific components and contents in the electrolyte of the present application can be determined by methods known in the art. For example, they can be determined by gas chromatography, gas chromatography-mass spectrometry (GC-MS), ion chromatography (IC), liquid chromatography (LC), nuclear magnetic resonance spectroscopy (NMR), inductively coupled plasma optical emission spectroscopy (ICP-OES), etc.
[0170] In some embodiments of the present application, the secondary battery further includes a positive electrode sheet, the positive electrode sheet includes a positive electrode active material, and the specific surface area of the positive electrode active material is 8m 2 / g~17m 2 / g.
[0171] The specific surface area in this application includes any conventional meaning in the art, and can be obtained by testing using instruments or methods known in the art, such as testing the specific surface area using a gas adsorption method, specifically referring to the standard test of GB / T19587-2017.
[0172] The specific surface area of the positive electrode active material selected in this application is relatively large. The positive electrode active material with this specific surface area is used in combination with the negative electrode active material protected in this application. Under the premise of reducing gas production, the rate performance and cyclability of the battery can be taken into account. In these embodiments, this application discloses that the specific surface area of the positive electrode active material can be 8m 2 / g, 8.5m 2 / g, 9m 2 / g, 9.5m 2 / g, 10m 2 / g, 12m 2 / g, 14m 2 / g, 16m 2 / g, 18m 2 / g or any of the values satisfying the above ranges.
[0173] In some embodiments of the present application, the positive electrode active material includes a lithium-containing transition metal phosphate.
[0174] The positive electrode active material selected in the present application includes a lithium-containing transition metal phosphate, which is selected to meet the above-mentioned specific surface area. On the other hand, the lithium-containing transition metal phosphate as a positive electrode active material in a secondary battery also has an obvious defect of high rate of return. The use of the negative electrode and electrolyte of the present application is conducive to improving this problem.
[0175] The lithium-containing transition metal phosphate in the present application comprises olivine-type lithium iron manganese phosphate, the chemical formula of which is Li (1-x1) Fe x2 Mn (1-x2) PO4, wherein 0≤x1<1, 0≤x2≤1. The battery formed by assembling the positive electrode active material with the above chemical formula in the present application will be accompanied by lithium deintercalation and consumption during the charging and discharging process. The molar content of lithium is different when the battery is discharged to different states. The above definition includes the lithium content of the battery under different charging and discharging states at a voltage of 2V to 5V.
[0176] The positive electrode sheet of the present application includes a positive electrode current collector and a positive electrode film layer, and the positive electrode film layer can be formed on one or two surfaces of the positive electrode sheet. In addition to the above-mentioned positive electrode active material, the positive electrode film layer also includes a positive electrode conductive agent and a positive electrode binder. The present application discloses in these embodiments that the mass ratio satisfies: lithium-containing transition metal phosphate: positive electrode conductive agent: positive electrode binder is (90% to 98%): (0.5% to 5%): (0.5% to 5%). Among them, the positive electrode conductive agent includes but is not limited to one or more combinations of graphite, superconducting carbon, carbon black (such as acetylene black, Ketjen black, Super P, etc.), carbon dots, carbon nanotubes, graphene and carbon nanofibers. The positive electrode binder includes but is not limited to one or a combination of two or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorine-containing acrylate resin, styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid, carboxymethyl chitosan, etc.
[0177] In some embodiments of the present application, the preparation method of the positive electrode sheet comprises: mixing each component with a solvent in a certain mass ratio to obtain a positive electrode slurry, coating the positive electrode slurry on one or two surfaces of the positive electrode current collector, heating, drying, and cooling to obtain a positive electrode sheet comprising a positive electrode film layer. The present application discloses in these embodiments that the heating and baking temperature is 90°C to 120°C, for example, it can be 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, etc. By regulating the baking temperature, the positive electrode active material and additives will not be thermally decomposed due to overheating on the basis of promoting the solvent volatilization and curing of the slurry. At the same time, the solvent used to prepare the positive electrode slurry includes one or more of N-methylpyrrolidone (NMP), N, N-dimethylformamide (DMF), N, N-diethylformamide (DEF), dimethyl sulfoxide (DMSO), pyridine and tetrahydrofuran (THF). By selecting these solvents, the stability and uniformity of the positive electrode active material in the slurry can be improved; at the same time, the solubility of the additives in the slurry can be improved, and the problems of slurry instability, easy stratification, and sedimentation can be solved. The selected solvent is a non-aqueous system, which can solve the problem of thermal hydrolysis of the additives.
[0178] The present application also discloses in some embodiments that the positive electrode current collector may be a metal foil or a composite current collector, wherein the metal foil may be an aluminum foil, and the composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and the like.
[0179] Isolation film
[0180] In some embodiments, the secondary battery further comprises a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0181] In some embodiments, the isolation membrane includes a base material layer and a coating disposed on the surface of the base material layer; the base material of the base material layer includes one or more of polyethylene, polypropylene, poly(p-phenylene terephthalamide), polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide and polyamide; the coating includes a ceramic coating and / or a polymer coating. The base material layer has a good permeability to lithium ions, which is beneficial to the migration of lithium ions; the surface of the base material layer is provided with a coating, and the coating can further improve the mechanical properties of the isolation membrane. Optionally, the ceramic particles in the ceramic coating include one or more of SiO2, Al2O3, AlOOH, CaO, TiO2, MgO, ZnO, ZrO2, Mg(OH)2 and BaSO4. Optionally, the polymer material of the polymer coating includes one or more of polyethylene (PE), polypropylene (PP), polyphenylene terephthalamide (PPTA), polyethylene terephthalate (PET), polytetrafluoroethylene (PTFE), polyacrylonitrile (PAN), polyimide (PI) and polyamide (PA). The polymer coating and the base material layer can be made of the same or different materials, and the thickness of the polymer coating and the base material layer can be different. Optionally, the thickness of the polymer coating is less than the thickness of the base material layer.
[0182] In other embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0183] Example
[0184] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0185] Example 1
[0186] 1. Preparation of negative electrode active material-artificial graphite
[0187] S1: Feed the needle-shaped raw petroleum coke raw material to the air flow crusher through a vibrating feeder for coarse crushing, then send the qualified material to the mechanical mill for fine crushing, use a grading screen to remove particles with a Dv50 of less than 1.1μm, and then polish the obtained particles to obtain a precursor with a Dv50 of 15μm;
[0188] S2: Add the precursor obtained in step S1 to the reactor, and add 10% of the binder asphalt (Dv50 is 7.5 μm) relative to the weight of the precursor for granulation for granulation, stir at a speed of 1200 r / min, heat to 560°C at a rate of 10°C / min at room temperature, and then keep the temperature constant for 8 hours, granulate until Dv50 is 20 μm, and obtain intermediate 1;
[0189] S3: Add the intermediate 1 obtained in step S2 into a graphitization furnace, heat it to 2100°C to 2150°C for graphitization, and sieve it with a 200-mesh sieve to obtain artificial graphite with a Dv50 of 18.5 μm, a Dv90 of 30 μm, a Dv10 of 6.5 μm, and a Dvl of 3 μm. The specific surface area of the artificial graphite is 0.52 m 2 / g, and the orientation index OI value of the artificial graphite is shown in Table 1.
[0190] 2. Preparation of negative electrode sheet:
[0191] The artificial graphite prepared above, the conductive agent conductive carbon, the stabilizer sodium carboxymethyl cellulose and the binder SBR were dispersed in deionized water in a mass ratio of 94.5:1.5:1.5:2.5 to form a negative electrode slurry. The negative electrode slurry was evenly coated on both sides of the negative electrode current collector copper foil, and dried in a nine-section oven with the temperature settings of 100°C / 100°C / 95°C / 85°C / 85°C / 80°C / 80°C / 80°C / 60°C, and then compacted using a cold press to make the single-sided coating weight of the negative electrode film layer 0.15g / 1540.25mm 2 .
[0192] 3. Preparation of electrolyte:
[0193] In an environment where the water content is less than 10 ppm, non-aqueous organic solvents ethylene carbonate and dimethyl carbonate are mixed in a volume ratio of 1:1 to obtain a first solvent, ethyl acetate and propyl acetate are mixed in a volume ratio of 2:1 to obtain a second solvent, the first solvent and the second solvent are mixed in a certain amount to form a non-aqueous solvent, lithium salt lithium hexafluorophosphate is added to the non-aqueous solvent, and then a film-forming stabilizer (lithium fluorosulfonate and lithium difluorophosphate) is added to form an electrolyte. The content of each component in the electrolyte is shown in Table 2.
[0194] 4. Preparation of positive electrode sheet:
[0195] Lithium iron manganese phosphate (chemical formula LiFe 0.5 Mn 0.5 PO4, specific surface area BET is 16.7m 2 / g): positive electrode conductive agent carbon black: positive electrode binder polyvinylidene fluoride (PVDF) is dispersed in an appropriate amount of solvent NMP according to 98:0.9:1.1 and fully stirred to form a uniform positive electrode slurry; the positive electrode slurry is coated on the two surfaces of the positive electrode current collector, heated and dried, specifically using a multi-section oven with the temperature settings of 120℃ / 100℃ / 90℃, and then compacted using a cold press to obtain a positive electrode sheet with a compaction density of 2.7g / cm 3 The positive electrode sheet has a single-sided coating weight of 0.34g / 1540.25mm 2 .
[0196] 5. Isolation film;
[0197] A porous polyethylene (PE) film was used as the isolation membrane.
[0198] 6. Preparation of secondary batteries:
[0199] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0200] Example 2
[0201] A secondary battery is provided. The difference between the secondary battery and the embodiment 1 is that the particle size and specific area of the artificial graphite are different, which is ultimately reflected in the different preparation methods of the artificial graphite, as follows:
[0202] S1: Feed the needle-shaped coal-based raw tar raw material to the air flow crusher through a vibrating feeder for coarse crushing, then send the qualified material to the mechanical mill for fine crushing, use a grading screen to remove particles with a Dv50 of less than 1.0 μm, and then polish the obtained particles to obtain a precursor with a Dv50 of 13 μm;
[0203] S2: Add the precursor obtained in step S1 to the reactor, and add 10% of the binder asphalt (Dv50 is 8 μm) relative to the weight of the precursor for granulation for granulation, stir at a speed of 1000 r / min, heat to 550°C at a rate of 10°C / min at room temperature, and then keep the temperature constant for 8 hours, granulate until Dv50 is 17.1 μm, and obtain intermediate 1;
[0204] S3: Add the intermediate 1 obtained in step S2 into a graphitization furnace, heat it to 2150°C to 2180°C for graphitization, and sieve it with a 200-mesh sieve to obtain artificial graphite with a Dv50 of 15.4 μm, a Dv90 of 35.6 μm, a Dv10 of 3.5 μm, and a Dvl of 2.5 μm. The specific surface area of the artificial graphite is 1.83 m 2 / g. And the orientation index OI value of the artificial graphite is shown in Table 1.
[0205] Example 3
[0206] A secondary battery is provided. The difference between the secondary battery and the embodiment 1 is that the particle size and specific area of the artificial graphite are different, which is ultimately reflected in the different preparation methods of the artificial graphite, as follows:
[0207] S1: Feed the needle-shaped raw petroleum coke raw material to the air flow crusher through a vibrating feeder for coarse crushing, then send the qualified material to the mechanical mill for fine crushing, use a grading screen to remove particles with a Dv50 of less than 0.8μm, and then polish the obtained particles to obtain a precursor with a Dv50 of 8.5μm;
[0208] S2: Add the precursor obtained in step S1 to the reactor, and add 12% of the binder asphalt (Dv50 is 7.5 μm) relative to the weight of the precursor for granulation for granulation, stir at a speed of 1300 r / min, heat to 570°C at a rate of 10°C / min at room temperature, and then keep the temperature constant for 8 hours, granulate until Dv50 is 10.4 μm, and obtain intermediate 1;
[0209] S3: Add the intermediate 1 obtained in step S2 into a graphitization furnace, heat it to 2100°C to 2150°C for graphitization, and sieve it with a 200-mesh sieve to obtain artificial graphite with Dv50 of 7.8 μm, Dv90 of 22.3 μm, Dv10 of 3.5 μm, and Dvl of 1.9 μm. The specific surface area of the artificial graphite is 2.5 m2 / g. And the orientation index OI value of the artificial graphite is shown in Table 1.
[0210] Example 4-1
[0211] A secondary battery is provided, which is different from Example 1 in that the negative electrode active material comprises the artificial graphite of Example 1 and further comprises hard carbon. Particles with a volume distribution particle size of less than 1.5 μm in the hard carbon are removed and then mixed with the artificial graphite.
[0212] The Dv50 of the hard carbon is 7.0 μm. The mass percentage of the hard carbon in the negative electrode active material is 20%, and the remaining 80% is the artificial graphite of Example 1. The specific surface area of the negative electrode active material is 0.83 m 2 / g.
[0213] Example 4-2
[0214] A secondary battery is provided, which is different from Example 4-1 in that the mass percentage content of hard carbon in the negative electrode active material is 10%, and the remaining 90% is the artificial graphite of Example 1, and the specific surface area of the negative electrode active material is 0.68m 2 / g.
[0215] Example 4-3
[0216] A secondary battery is provided, which is different from Example 4-1 in that the mass percentage content of hard carbon in the negative electrode active material is 5%, and the remaining 95% is the artificial graphite of Example 1, and the specific surface area of the negative electrode active material is 0.60m 2 / g.
[0217] Example 4-4
[0218] A secondary battery is provided, which is different from Example 4-1 in that the Dv50 of the hard carbon in the negative electrode active material is 5.0 μm, and the specific surface area of the negative electrode active material is 0.90 m 2 / g.
[0219] Embodiment 4-5
[0220] A secondary battery is provided, which is different from Example 4-1 in that the Dv50 of the hard carbon in the negative electrode active material is 3.5 μm, and the specific surface area of the negative electrode active material is 1.0 m 2 / g.
[0221] Example 5
[0222] A secondary battery is provided, which is different from Example 1 in that the negative electrode active material comprises the artificial graphite of Example 1 as a raw material, which is placed in an inert atmosphere furnace, and methane gas (the volume percentage of methane gas is 10%, and the gas flow rate is 1.0 L / min) is introduced into the inert atmosphere, and the temperature is controlled to be about 1000° C. The reaction is carried out for 3 to 4 hours, and an amorphous carbon coating layer is generated on the surface of the artificial graphite. The thickness of the carbon coating layer is nanometer-level, about 10 nm, and the content of artificial graphite is about 80%, forming a carbon material with a core-shell structure. The volume distribution particle size of the carbon material with the core-shell structure satisfies: Dv50 is 19 μm, Dv90 is 30.2 μm, Dv10 is 6.8 μm, and Dvl is 3 μm. The specific surface area of the carbon material is 0.50 m 2 / g, and the orientation index OI value of the carbon material is shown in Table 1.
[0223] Embodiment 6 to Embodiment 12 provide a secondary battery, wherein the negative electrode active material of the secondary battery is the same as that of Embodiment 1.
[0224] Table 1-1 Negative electrode active material properties
[0225]
[0226] Table 1-2 Graphitized carbon material properties list
[0227]
[0228]
[0229] Embodiments 6 to 10
[0230] A secondary battery is provided, which is different from Example 1 in that the electrolyte is different, as shown in Table 2. Among them, the content of carboxylic acid ester in Example 6 and Example 7 is different from that in Example 1 to Example 5, the content of carbonate ester is different from that in Example 1 to Example 5, and the content and type of film-forming stabilizer are different from those in Example 1 to Example 5. The type of carboxylic acid ester in Example 8 and Example 9 is different from that in Example 1 to Example 5. The type of film-forming stabilizer in Example 10 is different from that in Example 1 to Example 5.
[0231] Table 2 Electrolyte performance list
[0232]
[0233]
[0234]
[0235] Embodiment 11
[0236] A secondary battery is provided, which is different from Example 1 in that the specific surface area of the positive electrode active material is 10 m 2 / g, see Table 2 for details.
[0237] Example 12
[0238] A secondary battery is provided, which is different from Example 1 in that the specific surface area of the positive electrode active material is 8 m 2 / g, see Table 2 for details.
[0239] Comparative Example 1
[0240] A secondary battery is provided, which is different from that in Example 1 in that a battery with a specific surface area of 5.0 m 2 / g of artificial graphite is used as the negative electrode active material, and the small particle size materials in the artificial graphite are not controlled, so that it contains particles with a particle size of less than 1.5μm, and the volume content of this part of particles accounts for about 1%, see Tables 1-1, 1-2 and 2 for details.
[0241] Comparative Example 2
[0242] A secondary battery is provided. The difference between the secondary battery and the embodiment 1 is that the electrolyte contains only carbonate solvents and no carboxylate solvents are used, as shown in Tables 1-1, 1-2 and 2 for details.
[0243] Comparative Example 3
[0244] A secondary battery is provided. The difference between the secondary battery and Example 1 is that the electrolyte does not contain a film-forming stabilizer, as shown in Tables 1-1, 1-2 and 2 for details.
[0245] [Performance test of negative electrode active materials]
[0246] ①Test volume distribution particle size:
[0247] Referring to GB / T 19077-2016, the volume particle size distribution curve of the negative electrode active material is obtained, and the particle size corresponding to the cumulative volume distribution percentage reaching 50% is taken as the average particle size Dv50, the particle size corresponding to the volume distribution percentage reaching 90% is taken as Dv90, the particle size corresponding to the volume distribution percentage reaching 10% is taken as Dv10, and the particle size corresponding to the volume distribution percentage reaching 1% is taken as Dv1. The testing instrument can be the Mastersizer3000 laser particle size analyzer of Malvern Instrument Co., Ltd., UK.
[0248] Specifically, a laser particle size analyzer (Malvern 3000, MasterSizer 3000) is used for testing, and a helium-neon red light source is used as the main light source. Take a clean small beaker and add 1g of the sample to be tested, add 20mL of deionized water (the sample concentration ensures that the shading degree is 8-12%), add a drop of surfactant to reduce the surface tension of the water to facilitate the infiltration of the particles, and ultrasonicate at 53KHz / 120W for 5 minutes to ensure that the sample is completely dispersed. Turn on the laser particle size analyzer, clean the optical path system, and automatically test the background. Stir the ultrasonicated solution to be tested to make it evenly dispersed, put it into the sample cell as required, and start measuring the particle size. The measurement results can be read from the instrument.
[0249] ②Test specific surface area;
[0250] Referring to GB / T 19587-2004, the specific surface area of the negative electrode active material and / or the positive electrode active material is measured by nitrogen adsorption specific surface area analysis and testing method, and the specific surface area of the negative electrode active material and / or the positive electrode active material is calculated by BET (Brunauer Emmett Teller) method. The testing instrument can be TRISTAR II 3020 specific surface area and porosity analyzer from Micromeritics, USA.
[0251] ③Test orientation index OI value;
[0252] The graphitized carbon material is placed on an X-ray powder diffractometer for detection to obtain the peak intensity values of the plane (110) and the plane (004) of the graphite crystal. The orientation index OI value can be obtained by calculating the peak integrated area ratio of the two crystal planes.
[0253] [Battery performance test]
[0254] ④High temperature gas production test:
[0255] The prepared battery was charged to 100% SOC at a rate of 0.1C and stored at 60°C. The internal pressure of the battery was monitored online using a barometer. When the cut-off pressure was 0.35MPa, the number of days stored at 60°C was recorded. The test results are shown in Table 3.
[0256] ⑤Test of fast charging capability:
[0257] The batteries of the above embodiments and comparative examples were charged and discharged for the first time at a current of 1C (i.e., the current value at which the theoretical capacity is completely discharged within 1 hour), specifically comprising: at 35°C, the battery was charged at a constant current rate of 1C to a voltage of 4.4V, then charged at a constant voltage to a current ≤0.05C, left to stand for 5 minutes, and then discharged at a constant current rate of 0.33C to a voltage of 2.8V, and its actual capacity was recorded as C0. Then the battery is charged with constant current of 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, 3.0C0, 3.5C0, 4C0, 4.5C0, 5C0 in sequence to the full battery charge cut-off voltage of 4.4V or 0V negative electrode cut-off potential (whichever is reached first). After each charge is completed, it is necessary to discharge with 1C0 to the full battery discharge cut-off voltage of 2.8V. Record the SOC (State of Charge) at different charge rates to 10%, 20%, 30%, ..., 80% Charge, when "SOC = 0" means the battery is fully discharged, when "SOC = 100%" means the battery is fully charged) the corresponding negative electrode potential, draw the charging rate negative electrode potential curve under different SOC states, and obtain the charging rate corresponding to the negative electrode potential of 0V under different SOC states after linear fitting. The charging rate is the charging window under the SOC state, which is recorded as C10%SOC, C20%SOC, C30%SOC, C 40% SOC, C50% SOC, C60% SOC, C70% SOC, C80% SOC, according to the formula (60 / C20% SOC+60 / C30% SOC+60 / C40% SOC+60 / C50% SOC+60 / C60% SOC+60 / C70% SOC+60 / C80% SOC)×10%, the charging time T of the battery from 10% SOC to 80% SOC is calculated in min. The shorter the time, the better the fast charging performance of the battery.
[0258] ⑥Cyclic performance test:
[0259] At 45°C, the secondary battery prepared in the embodiment and comparative example is charged to 3.75V at a constant current of 1C (i.e., the current value that completely discharges the theoretical capacity within 1 hour), then charged to 0.05C at a constant voltage of 3.75V, left to stand for 5 minutes, and then discharged to 2.5V at a constant current of 1C, left to stand for 30 minutes. This is a charge and discharge cycle process, and the battery capacity C0 at this time is recorded. According to this method, the battery is charged and discharged for n cycles, and the battery capacity after n cycles is recorded as C1. Then the cycle capacity retention rate of the battery at 25°C = C1 / C0×100%. Record the number of cycles n corresponding to the measured cycle capacity retention rate of the battery of 80%.
[0260] Table 3 Battery performance list
[0261]
[0262]
[0263] Combined with the embodiment of Table 3 and comparative example 1, if the specific surface area of the negative electrode active material is not controlled, and the active material content of the small particles is not controlled, the cycle stability and fast charging performance of the secondary battery cannot be taken into account. Combined with comparative examples 2 and 3, it can be seen that when the electrolyte does not contain a carboxylic acid ester solvent, the battery's rate capability is poor, and when the film-forming stabilizer is not contained, the battery's cycle stability deteriorates. Therefore, the present application controls the negative electrode active material so that the graphitized carbon material as the negative electrode active material has the characteristics of a small specific surface area and a small number of small-particle particles. The negative electrode active material having this characteristic is used in combination with an electrolyte containing a carboxylic acid ester solvent and a film-forming stabilizer. On the premise of improving the rate capability of the secondary battery, it can also reduce the impact on the battery cycle performance.
[0264] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A secondary battery, characterized in that: include: Negative electrode sheet: contains negative electrode active material, and the negative electrode active material meets the following conditions: (1.1) The BET specific surface area of the negative electrode active material is 0.5 m 2 / g~3.0m 2 / g; (1.2) The volume distribution particle size Dv1 of the negative electrode active material is ≥ 1.5 μm; The negative electrode active material comprises a graphitized carbon material; the orientation index OI value of the graphitized carbon material satisfies: 12≤OI value≤22; the orientation index OI value is the peak intensity ratio of the plane (110) to the plane (004) in the X-ray powder diffraction pattern of the graphitized carbon material; Electrolyte: comprising a carboxylic acid ester solvent and a film-forming stabilizer; and A positive electrode sheet, the positive electrode sheet comprising a positive electrode active material, the BET specific surface area of the positive electrode active material is 8m 2 / g~17m 2 / g.
2. The secondary battery according to claim 1, characterized in that: The BET specific surface area of the negative electrode active material is 0.5 m 2 / g~2.0m 2 / g; and / or; The volume distribution particle size Dv1 of the negative electrode active material is 1.9 μm to 3.1 μm.
3. The secondary battery according to any one of claims 1 to 2, characterized in that: The volume distribution particle size of the graphitized carbon material satisfies: 7.5 μm≤Dv50≤20 μm, Dv10≥3.5 μm, and Dv90≤40 μm.
4. The secondary battery according to claim 3, characterized in that: The volume distribution particle size of the graphitized carbon material satisfies: 10 μm≤Dv50≤18.5 μm, 3.5 μm≤Dv10≤7.0 μm, and Dv90≤40 μm.
5. The secondary battery according to any one of claims 1 to 2, characterized in that: The negative electrode active material further comprises amorphous carbon; the amorphous carbon comprises one or both of hard carbon and soft carbon; The volume distribution particle size of the amorphous carbon satisfies: 3.5 μm≤Dv50≤7.0 μm; and / or; The graphitized carbon material includes one or more of natural graphite, artificial graphite, and composite graphite.
6. The secondary battery according to claim 5, characterized in that: The graphitized carbon material has a core-shell structure, the core of the core-shell structure comprises one or more of natural graphite, artificial graphite, and composite graphite, and the shell of the core-shell structure comprises an amorphous carbon coating layer.
7. The secondary battery according to any one of claims 1 to 2, characterized in that: Based on the total mass of the negative electrode active material, the mass percentage content of the graphitized carbon material is greater than 75%.
8. The secondary battery according to any one of claims 1 to 2, characterized in that: The carboxylate solvent satisfies at least one of the following: (4.1) The carboxylic acid ester has the following structural formula: R1-COO-R2; wherein R1 and R2 each independently comprise a substituted and / or unsubstituted C1-C5 alkyl group; (4.2) Based on the mass of the electrolyte, the mass percentage content of the carboxylic acid ester is 5% to 70%.
9. The secondary battery according to claim 8, characterized in that: The carboxylate solvent satisfies at least one of the following: (5.1) The carboxylic acid ester comprises one or more of ethyl acetate, methyl acetate, ethyl propionate, propyl acetate, methyl propionate, and methyl butyrate; (5.2) Based on the mass of the electrolyte, the mass percentage content of the carboxylic acid ester is 10% to 60%.
10. The secondary battery according to claim 9, characterized in that: The electrolyte further comprises a carbonate solvent, and the carbonate solvent comprises one or more of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, vinylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
11. The secondary battery according to any one of claims 1 to 2, characterized in that: The film-forming stabilizer satisfies at least one of the following requirements: (6.1) Based on the total mass of the electrolyte, the mass percentage content of the film-forming stabilizer is 0.02% to 6%; (6.2) The film-forming stabilizer comprises one or more of a boron-containing lithium salt, a phosphorus-containing lithium salt and a sulfur-containing lithium salt; The boron-containing lithium salt includes one or more of lithium tetrafluoroborate, lithium bis(oxalatoborate) and lithium bis(fluorooxalatoborate); and / or; The phosphorus-containing lithium salt includes one or more of lithium difluorophosphate, lithium fluorophosphate and lithium phosphate; and / or; The sulfur-containing lithium salt includes one or more of lithium fluorosulfonate, lithium sulfate, and lithium aminosulfonate.
12. The secondary battery according to claim 11, characterized in that: The film-forming stabilizer comprises lithium fluorosulfonate and lithium difluorophosphate. Based on the total mass of the electrolyte, the mass percentage content of the lithium difluorophosphate is ≤1%, and the mass percentage content of the lithium fluorosulfonate is greater than or equal to 0.1% and less than 2%.
13. The secondary battery according to any one of claims 1 to 2, characterized in that: The positive electrode active material comprises a lithium-containing transition metal phosphate; The lithium-containing transition metal phosphate comprises olivine-type lithium manganese iron phosphate, and the chemical formula of the olivine-type lithium manganese iron phosphate is Li (1-x1) Fe x2 Mn (1-x2) PO4, where 0≤x1<1, 0≤x2≤1.
14. An electrical device, characterized in that: A secondary battery according to any one of claims 1 to 13.
Citation Information
Patent Citations
Lithium ion battery and cathode material thereof
CN108155351A
Electrolyte, secondary battery and electric equipment
CN115411363A
Secondary battery and electric device
CN117558918A
Secondary battery and preparation method therefor, and electric device
US20250007010A1